Realistic simulation of a Lego Mindstorms NXT based robot - Gonçalves, José (2010)
This paper describes the realistic simulation of a Lego Mindstorms NXT based robot. The presented approach does not replace the training with hardware but is an important complement, since it allows to develop robot software without accessing to the real hardware.